2022
DOI: 10.1002/ptr.7424
|View full text |Cite
|
Sign up to set email alerts
|

An extensive review on phytochemistry and pharmacological activities of Indian medicinal plant Celastrus paniculatus Willd

Abstract: Celastrus paniculatus is a traditional herb belonging to the family Celastraceae and is widely used for a number of medicinal activities in the Indian Unani and Ayurvedic systems. In this study, the extensive literature search was carried out on phytochemistry, ethnobotanical uses and pharmacological activities of C. paniculatus (Willd.) in various scientific databases as well as patents. Research on phytochemical investigation has shown the presence of monoterpenes (linalool, α‐terpinyl acetate, nerol acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The disruption of hydrogen bonding under high‐temperature stir‐frying conditions provides additional conformational degrees of freedom, allowing the glycosidic bond to be more readily protonated and the β‐glycosidic bond between the hydroxyl group at the 1‐position of the ceramide and the sugar moiety (D‐galactose or D‐glucose) to be cleaved with a much lower hurdle in turn (Paajanen et al., 2021 ). Plant sterol esters are generally synthesized from plant sterol and fatty acids by esterification or transesterification (Nagpal et al., 2022 ). As sitosterol ester (SiE) (20:5) and stigmasterol ester (StE) (19:2) were lower in C0, our findings indicated that stir‐frying treatment also destroyed sterol esters.…”
Section: Resultsmentioning
confidence: 99%
“…The disruption of hydrogen bonding under high‐temperature stir‐frying conditions provides additional conformational degrees of freedom, allowing the glycosidic bond to be more readily protonated and the β‐glycosidic bond between the hydroxyl group at the 1‐position of the ceramide and the sugar moiety (D‐galactose or D‐glucose) to be cleaved with a much lower hurdle in turn (Paajanen et al., 2021 ). Plant sterol esters are generally synthesized from plant sterol and fatty acids by esterification or transesterification (Nagpal et al., 2022 ). As sitosterol ester (SiE) (20:5) and stigmasterol ester (StE) (19:2) were lower in C0, our findings indicated that stir‐frying treatment also destroyed sterol esters.…”
Section: Resultsmentioning
confidence: 99%
“…This plant has been used for more than a thousand years in Indian Ayurvedic medicine, commonly called "the intellect tree", from Hindu, Malkangani. Celastrus paniculatus has therapeutic potential, from oil and methanol extract to seeds [72,73]. Its neuroprotective potential has already been tested for schizophrenia induced by ketamine in rats, treating the disorder combined with clozapine or alone.…”
Section: Celastrus Paniculatusmentioning
confidence: 99%
“…Estevez-Braun et al reported a polyacetylene C17 plant innate to the Canary islands, confined from Bupleurum salicifolium. 28 Aqueous extract of Celastrus paniculatus was found to be effective against bacterial and fungal strains owing to presence of phenolic components [29].…”
Section: Different Mixesmentioning
confidence: 99%